2021
DOI: 10.3390/ijms22157939
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis of Human Adipose-Derived Stem Cells Undergoing Osteogenesis in 2D and 3D Culture Conditions

Abstract: Human adipose-derived stem cells (hADSCs) are types of mesenchymal stem cells (MSCs) that have been used as tissue engineering models for bone, cartilage, muscle, marrow stroma, tendon, fat and other connective tissues. Tissue regeneration materials composed of hADSCs have the potential to play an important role in reconstituting damaged tissue or diseased mesenchymal tissue. In this study, we assessed and investigated the osteogenesis of hADSCs in both two-dimensional (2D) and three-dimensional (3D) culture c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Despite these limitations, 2D cell culture remains a valuable tool in the laboratory, and many advances were made in recent years to improve the system, such as techniques for analyzing and characterizing cells, such as high-content imaging and transcriptomics. These techniques allow for a more detailed understanding of the behavior and characteristics of cells in culture [ 104 , 105 ].…”
Section: Cell Culture System—from 2d To 3dmentioning
confidence: 99%
“…Despite these limitations, 2D cell culture remains a valuable tool in the laboratory, and many advances were made in recent years to improve the system, such as techniques for analyzing and characterizing cells, such as high-content imaging and transcriptomics. These techniques allow for a more detailed understanding of the behavior and characteristics of cells in culture [ 104 , 105 ].…”
Section: Cell Culture System—from 2d To 3dmentioning
confidence: 99%
“…Since they are stem cells, it is crucial to provide them with the proper signals so that they differentiate toward tendinocyte lines, and they do not differentiate toward osteogenic lines resulting in ECM characteristics of bone tissue rather than tendon tissue ( Loebel and Burdick, 2018 ). The most commonly used stem cells in tendon tissue engineering are MSCs ( Kim et al, 2021 ), TSPCs ( Zhang et al, 2019 ), and IPSCs ( Tsutsumi et al, 2022 ), which can also give rise to tendinocytes or fibroblasts after differentiation.…”
Section: Tissue Regeneration Strategies For Achilles Tendon Injury Tr...mentioning
confidence: 99%
“…Molecular and transcriptomic background of osteogenesis of hADSCs was studied by Kim and co-workers in two-dimensional (2D) and three-dimensional (3D) culture conditions [ 7 ]. The comprehensive transcriptome expression profiles during osteogenic differentiation of hADSCs under different culture conditions revealed that the genes related to bone development and bone remodeling processes were overexpressed in the 3D culture condition.…”
Section: Bone Regeneration Tissue Engineering and Msc Secretomementioning
confidence: 99%